2014
DOI: 10.1016/j.watres.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities from different types of natural wastewater treatment systems: Vertical and horizontal flow constructed wetlands and biofilters

Abstract: The prokaryotic microbial communities (Bacteria and Archaea) of three different systems operating in Denmark for the treatment of domestic wastewater (horizontal flow constructed wetlands (HFCW), vertical flow constructed wetlands (VFCW) and biofilters (BF)) was analysed using endpoint PCR followed by Denaturing Gradient Gel Electrophoresis (DGGE). Further sequencing of the most representative bacterial bands revealed that diverse and distinct bacterial communities were found in each system unit, being γ-Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(57 citation statements)
references
References 23 publications
7
50
0
Order By: Relevance
“…1), core genera populations existed in all the samples. Among the shared genera, members of Thauera, Rhodobacter, Hyphomicrobium and Paracoccus are functionally important denitrifiers as previously reported16. Planctomyces, Prirellula , and Gemmata , which belong to the Planctomycetes phylum, are considered major players in the global nitrogen and carbon cycles.…”
Section: Discussionsupporting
confidence: 55%
“…1), core genera populations existed in all the samples. Among the shared genera, members of Thauera, Rhodobacter, Hyphomicrobium and Paracoccus are functionally important denitrifiers as previously reported16. Planctomyces, Prirellula , and Gemmata , which belong to the Planctomycetes phylum, are considered major players in the global nitrogen and carbon cycles.…”
Section: Discussionsupporting
confidence: 55%
“…The COD and nitrification removal rates were also higher than several reported in literature [73,84,112]. Although there are few studies on removal kinetics changes in organic compounds by heavy metal-tolerant bacteria, those results have been the most forceful.…”
Section: Isolated Consortium From Acid Mine Drainsmentioning
confidence: 69%
“…Most of the constructed wetlands (CW) studies indicate that microorganisms are the main component of these treatment systems, because they interact more with wastewater, packing medium and vegetation to achieve the removal of contaminants [34,[72][73][74][75].…”
Section: Role Of Microorganisms In Cw Treating Acid Mine Drainage Conmentioning
confidence: 99%
“…Despite CWs have been traditionally considered as 'black boxes', the research and technical development in the technology over the last decades has shown that the system's design and operation parameters influence the dominating environmental conditions inside the wetland, which, in turn affects degradation processes [9,10]. While dissolved oxygen concentration is one of the main limiting factors for biodegradation processes in traditional horizontal subsurface flow CW (HF) operating mostly under anoxic/anaerobic conditions due to the permanent saturation of the wetland bed, unsaturated vertical flow CW (VF) units were developed to increase the oxygen transfer capacity by specific design and operational conditions, such as intermittent feeding and resting periods [1,11].…”
Section: Introductionmentioning
confidence: 99%